Direitos autorais na cibercultura: previsão e alcance na legislação e jurisprudência brasileira - Hepp, Milena Brepohl (2023)
Aware of the transnational world and the experience of cyberculture, concerned with the technological advances made and the copyright of what circulates in the cyberspace, we wrote this dissertation. From a qualitative methodological bias (and at times quantitative), bibliographical and documental, we seek, through this dissertation, to investigate what is the scope of Copyright in relation to the phenomenon of cyberculture in Brazil. To do so, we analyze what Brazilian legislation provides for Copyright in relation to cyberculture and cyberspace and what are the jurisprudential supports. Through an interdisciplinary perspective, we explained, according to the works of Levy (1999), Lyotard (2009), Castells (1999), Dias and Sartori (2010), and others, more about postmodernity, cyberculture, cyberspace and transnationality and how these influenced the elaboration of the “Marco Civil da Internet”. Furthermore, we elucidated, following the insights of Lemos (2014), Pinheiro (2014, 2021), Bittar (2015), Zanini (2010), Wachowski (2012), more about intellectual property, copyright, and the legal and jurisprudential provisions concerning Copyright in Brazil. We delved into a corpus of Brazilian regulations collected and compiled by the Institute of Copyright Observatory (IODA), which included: Decree-law No. 2.848/1940, Decree No. 26.675/1949, Law No. 4.480/64, Decree-Law No. 980/1969, Decree No. 75.699/1975, Decree No. 76.905/75, Law 6.533/1978, Decree No. 82.385/197, TRIPS Agreement, Law 9.609/1998, Law 9.610/1998, Law 10.695/2003, Decree No 9.099/2017, Decree No. 9.522/2018, Decree No. 9.574/2018, and Decree No. 9.879/2019, as well as jurisprudential interpretations (provisions on copyright in: STF's general relevance rulings; STF and STJ's binding precedents; STJ's affectation rulings and repetitive appeals of STJ, as well as provisions on Copyright and cyberculture in TJPR's rulings). Our comprehensive analysis not only explored the content of these materials but also investigated the frequency of terms related to Copyright, Cyberculture, and Cyberspace. We established that the existing norms and jurisprudence don’t fully address the complexities of cyberculture, highlighting the need for updates or reform to not only embrace Cyberculture but also maintain a balance between the various interests in the discussions on copyright (commercial and educational). Lastly, we raise the point that our research opened space for further inquiries, with its applicability being relative. We hope that this investigation, grounded in the data collected and issues discussed, demonstrates the absence of specific Brazilian legal provisions concerning the intersection of Copyright and Cyberculture, thus encouraging a reform of the system.